HUBUNGAN LAMA PEMBERIAN ASI DENGAN STATUS GIZI BAYI - Paryono, Paryono; Astuti, Endah Widhi; Nabilah, Luthfi Azmatun (Tahta Media Group, 2023)
Background: Malnutrition early in life can result in growth failure. Several efforts to improve malnutrition include giving only breast milk to babies from birth to 6 months of age. Most babies who receive exclusive breast milk have good nutritional status compared to babies who do not receive exclusive breast milk. Research Objective: To determine the relationship between the duration of breastfeeding and the nutritional status of 6 month old babies in the Karanganom Klaten Community Health Center working area. Methods: Quantitative research type with an analytical observational design with a cross sectional design. Samples were taken using purposive sampling as many as 52 babies aged 6 months. Data analysis using the Spearman rank correlation test at a significance level of 0.05. Results: The duration of breastfeeding alone for babies up to 6 months of age is presented in table 4.1. while the nutritional status of babies up to 6 months of age is in table 4.2. The relationship between the duration of breastfeeding and the nutritional status of babies aged 6 months with a correlation of 0.797, p value 0.000. Conclusion: There is a significant relationship between the duration of breastfeeding with the nutritional status of 6 month old babies in the Karanganom Klaten Community Health Center working area.